1985
DOI: 10.1002/pol.1985.180231212
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the γ form and the development of the α form in nylon 6

Abstract: The structure of nylon 6 fibers is analyzed by x‐ray diffraction. Our results suggest that only two forms of nylon 6, α and γ, along with lattice distortion and crystallite size, are sufficient to explain the whole range of crystalline structures observed in nylon 6. The γ phase is the preferred initial form in a number of nylon 6 samples. The lattice distortion of the γ form along the chain axis varies from 0.8 to 2.4%, depending on the processing conditions. Upon annealing nylon 6 fibers, the α form is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 14 publications
4
106
1
Order By: Relevance
“…113 Moisture that enables PA-6 to crystallize preferentially in the a-crystalline form at ambient temperatures 39,114 causes it to crystallize completely in the a form at high temperatures and even brings about transformation of the c form into the a form. 28,105,115 Because water (solvent) molecules diffuse preferentially into the amorphous regions, these data show that the interactions between the crystalline stems and amorphous segments are bidirectional; that is, an increase in the mobility of the amorphous chains can affect the motion of the crystalline stems. In fact, it has been shown that amorphous segments interact with the crystalline stems at the interface, preferentially with the bc plane (b being the chain axis).…”
Section: Interaction Between Amorphous and Crystalline Domainsmentioning
confidence: 97%
See 3 more Smart Citations
“…113 Moisture that enables PA-6 to crystallize preferentially in the a-crystalline form at ambient temperatures 39,114 causes it to crystallize completely in the a form at high temperatures and even brings about transformation of the c form into the a form. 28,105,115 Because water (solvent) molecules diffuse preferentially into the amorphous regions, these data show that the interactions between the crystalline stems and amorphous segments are bidirectional; that is, an increase in the mobility of the amorphous chains can affect the motion of the crystalline stems. In fact, it has been shown that amorphous segments interact with the crystalline stems at the interface, preferentially with the bc plane (b being the chain axis).…”
Section: Interaction Between Amorphous and Crystalline Domainsmentioning
confidence: 97%
“…In fact, hydration depresses all the temperature-related transitions by about 70 8C: the a process is depressed by 40 8C by 2-3% water; 3 T B is depressed by 70 8C; the temperature at which the crystallization rate is maximum is reduced by as much as 70 8C (unpublished results); and the transformation from c to a occurs at 215 8C in dry PA-6 and at 160 8C in water (accompanied by hydrolysis). 20,28 Likewise, the effects of water are considerably enhanced at elevated temperatures.…”
Section: Chain Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is an indication that the PA9-T crystals have a much higher resistance to moisture in comparison to that of nylon 6 crystals. Although most of the water is considered to penetrate into the amorphous regions, there have been some suggestions that water can also affect the ordering of crystalline regions 17,19,25,26 . To examine this, the structural changes in the crystalline regions of PA9-T and nylon 6 accompanying hydration were investigated further.…”
Section: Humidity-controlled Dva Measurementmentioning
confidence: 99%